2004
DOI: 10.1016/s0272-6386(04)00958-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of mortality associated with hip fracture in the dialysis population

Abstract: Hip fracture is associated with an increased risk of all-cause mortality in the dialysis population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 0 publications
3
92
0
1
Order By: Relevance
“…Mittalhenkle et al [46] firstly focused on hip fracture and found that hip fracture was significantly correlated with high all-cause mortality in dialysis patients. In this study, we found that the CV events and all-cause death in the FF group were all higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Mittalhenkle et al [46] firstly focused on hip fracture and found that hip fracture was significantly correlated with high all-cause mortality in dialysis patients. In this study, we found that the CV events and all-cause death in the FF group were all higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hip fracture was associated with a twofold increase in the incident rate ratio for all-cause mortality in dialysis patients. Mortality secondary to cardiovascular disease, infection, metabolic causes and malnutrition were 2-to 3-fold higher in patients with hip fracture compared to the non-fracture group [4]. In a retrospective analysis of 1,272 patients on hemodialysis, the incidence of hip fracture was 13.9 per 1,000 patient-years [3].…”
Section: Bmd and Fracture Risk In Renal Failurementioning
confidence: 94%
“…The incidence of fractures is much higher in these patients compared to the general population [1][2][3]. Furthermore, mortality associated with hip fractures is higher in these patients compared to the general population [4]. In addition, there is an increasing amount of evidence suggesting a potential link between bone and mineral metabolism and cardiovascular disease [5,6], therefore the term CKD-mineral and bone disorder (CKD-MBD) has been suggested to describe the complexity of the syndrome [7].…”
mentioning
confidence: 99%
“…Besides, several medical and nonmedical factors have been associated with the mortality rate from hip fractures. Compared with the general population, patients with end-stage renal disease have significantly higher mortality rates after hip fracture [9]. Poor hygiene in assisted care and hospital settings can also increase mortality rates after a hip fracture [10,11].…”
Section: Introductionmentioning
confidence: 99%